Multisystem Inflammatory Syndrome in an Adult (MIS-A) Successfully Treated with Anakinra and Glucocorticoids - Paolo Cattaneo; Alessandro Volpe; Chiara Simona Cardellino; Niccolò Riccardi; Giulia Bertoli; Tamara Ursini; Arjola Ustalli; Giovanni Lodi; Ivan Daroui; Andrea Angheben (Microorganisms, 2021)
During the current SARS-CoV-2 pandemic, a novel syndrome termed “multisystem inflammatory syndrome in children” (MIS-C) has emerged. MIS-C was linked to COVID-19 and shared some features with Kawasaki disease and Toxic Shock Syndrome, with a common pathogenetic substrate of hyperinflammation and cytokine storm. Lately, MIS was also described in adults (≥21 years of age) and named “MIS-A”. There is no consensus about the treatment of MIS-A; successful use of glucocorticoids and immunoglobulins has been reported in case series, but more solid evidence is lacking. Furthermore, the role of biologic agents with proven benefits against COVID-19, MIS-C, or Kawasaki disease is still unexplored. In this report, we detail the clinical picture and the diagnostic process that led to the diagnosis of MIS-A in a 27-year-old man, focusing on its treatment with anakinra and glucocorticoids, which resulted in full recovery. To our knowledge, this is the first report of the successful use of anakinra for MIS-A, a drug that has already proven useful in the treatment of refractive cases of MIS-C. Anakinra may also play a pivotal role for the treatment of MIS-A.